Swedish Business R&D and its Export Dependence - Karin Bergman; Olof Ejermo (Lund University, School of Economics and Management, Department of Economics, 2011)
Sweden has seen a rise in business R&D-intensities and dependence on exports to make its economy grow since the early 1990s. This paper examines the role of foreign sales in stimulating R&D as compared to a domestic sales effect, and finds, in line with the literature, that R&D rises proportionally to sales in cross-sections from 1991 to 2001. Among manufacturing firms, foreign sales are distinctly more associated with an increase in R&D than domestic sales. For service firms, domestic sales are as important as foreign. The results are consistent with the hypotheses that manufacturing firms more easily separate production from R&D, economize on transport costs and are subject to learning-by-exporting effects. In general, the results highlight the dependence on openness in stimulating R&D in a small economy, especially among manufacturing firms.
Keywords: D22; L23; O32; 330; R&D; size; exports; Sweden